Методика визначення рівню специфічності промислової продукції виробничого підприємства - Яцина, Вікторія Валентинівна (НТУ "ХПІ", 2015)
Обґрунтовано необхідність аналізу складу промислової продукції виробничих підприємств за рівнем специфічності. Запропоновано методику визначення ступеню специфічності товарів, що дозволяє ранжувати їх за атрибутами специфічності. Методика заснована на використанні методів експертних оцінок з використанням вагових коефіціентів та кластерного аналізу. Визначено основні параметри специфічності товарів та розроблено їх оцінну шкалу. Зроблено висновки про необхідність врахування рівня специфічності товару при виборі типів контракту на його виробництво та реалізацію.

The necessity of industrial goods analysis at the production enterprises according to the specificity level has been grounded. The method of determining the level of goods specificity, which allowing to rank industrial products in accordance theirs attributes specificity has been proposed. The method is based on the expert evaluations using weighted coefficients and cluster analysis. The main parameters of goods specificity and their evaluative scale have been defined. The result of the method application was division of production enterprises industrial products on three types: idiosyncratic or unique goods, imperfectly simulated or difficult reproductive goods and standardized. The conclusions about the necessity of considering the specificity level of the product types during the process of choosing a production and sale contract have been made. The specificity rising leads to some interdependence between the manufacturer and the customer, as a result, the contracting parties can violate an agreement, which have been concluded earlier. The way of avoiding these circumstances is detailed consideration of contract conditions with theirs securing legal. This can only be prevented with detailed terms of the agreement, legally enshrined in the contract. Therefore, for idiosyncratic and imperfectly simulated goods it is advisable the classical and neoclassical contract conclusion. For standardized goods the conditions of implicit contract have been proposed.
Methods of determining the specificity level of production enterprise industrial products
Keywords: товар; специфічність активів; атрибути специфічності; метод експертних оцінок; кластерний аналіз; goods; assets specificity; attributes specificity; cluster analysis